Above-ground net primary productivity and rain use efficiency of Chaco Semi-arid Forest in Copo National Park, Santiago del Estero, Argentina - Tiedemann, José L. (2023)
According to the REDD + Program, it is necessary to monitor, quantify and report the forest system status of protected areas. Having this in mind the objective of this work is to delimit the growing seasons of Chaco Semi-arid Forest (FCHS) in Copo National Park (CNP), Santiago del Estero, Argentina, in the 2000-2022 period using time series of NDVIMODIS., and to quantify their Seasonally Integrated Aboveground Net Primary Productivity (SI-ANPP), its trend, and Rain Use Efficiency (RUE), and relate them to integrated seasonal rainfall (SR). The NDVIMODIS time series and the 0.5 NDVIRATIO thresholds made it possible to delimit the growth season, and quantify the SI-ANPP of FCHS with high efficiency. Significant differences were found (T = -3.49; p = 0.0006) in the SI-ANPP of FCHS. The SI-ANPP evidences high sensitivity to negative anomalies of seasonal rainfalls. The nonlinear regression model obtained (R2 = 0.73; p < 0.0001) provides unedited information at the local level on the efficiency of the SI-ANPP in terms of the SR. Seasonal rainfall >700 mm could be considered a threshold (or boundary) in the efficient water use of FCHS. The large positive trend of SI-ANPP of the FCHS CNP in the period 2000-2022 (slope = 462.43; T = 25.64; p <0.0001) evidenced the high stability of the forest system. The results obtained reaffirm the importance of creating legally protected areas, such as national parks, for the preservation of forest systems in the region.